Safety and efficacy of immune checkpoint inhibitors in patients with pre-treatment reduced left ventricular function - Maor Tzuberi; Rafael Y. Brzezinski; Nir Flint; Moaad Slieman; Lior Zornitzki; Dana Viskin; Anna Rozenfeld Hemed; Barliz Waissengrin; Renana Barak; Inbal Golomb; Ido Wolf; Netanel Golan; et al. (Cardio-Oncology)
Abstract Aims Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment outcomes. However, the response varies across different populations, and their use may lead to life-threatening cardiovascular (CV) events. While pre-treatment reduced left ventricular ejection fraction (LVEF) is considered a marker for high-risk cardiotoxicity and a contraindication for anthracycline and HER2-targeted therapies, there is limited evidence on the safety and efficacy of ICIs therapy in patients presenting with pre-treatment reduced LVEF. The study aims to evaluate the safety and efficacy of ICIs therapy in patients with pre-treatment reduced LVEF. Methods Retrospective single center cohort of patients treated with ICIs therapy, who performed pre-treatment LVEF assessment. The primary endpoint was to evaluate the safety of ICIs among this population, assessed by CV events (composite of myocarditis, acute coronary syndrome, heart failure, and arrhythmias). The secondary endpoint was to evaluate the efficacy of ICIs, assessed by all-cause mortality and progression-free survival (PFS). Results The cohort included 307 patients, with 30 (10%) presenting with pre-treatment reduced LVEF, with a mean LVEF of 39 ± 7%. While a significantly higher incidence of CV events was observed in the reduced LVEF group (37% vs. 14%, p = 0.004), following a multivariate Cox regression analysis including baseline CV diseases and risk factors, pre-treatment reduced LVEF did not remain a significant independent predictor (p = 0.358). No significant differences were observed between the groups regarding all-cause mortality and PFS. Conclusions Pre-treatment reduced LVEF was not identified as an independent marker for clinical outcomes in patients treated with ICIs therapy.